Significance of solar radiation and viscous dissipation on oscillatory and steady convective heat transfer around buoyancy-driven sphere using FDM scheme - Alanoud Alsuhaymi; Musaad S. Aldhabani (Case Studies in Thermal Engineering)
The innovation of this paper is to explore the transient behavior of heat transport and transient behavior of shear stress rate of unsteady fluid flow around the sphere surface in the presence of solar radiation, thermal buoyancy and viscous dissipation. Thermal radiation is used in the development of nuclear reactors, fire propagation, jet motion, chemical manufacturing, missile engine power, rockets, ships, space exploration, supersonic weapons, and gasoline turbines. The main theme of this examination is to generate the oscillations in heat frequency and oscillations in shear stress rate around a sphere surface. The governing mathematical model is solved by using primitive variable formulation and finite difference method. The formulated model is changed into global matrix form by using Gaussian elimination method. The effects of viscous dissipation N, thermal radiation Rd, buoyancy force λ and Prandtl parameter Pr on velocity distribution, temperature distribution, oscillatory shear stress and oscillatory heat transfer around three positions of buoyancy-driven sphere. In this proposal, the influence of various parameters on oscillatory shear stress and oscillatory heat transfer around different positions of heated sphere is drafted physically. It is depicted that the velocity distribution increases as viscous dissipation increases around position α=0.1 of sphere but the minimum velocity profile is noted around position α=1.0 of sphere. It is found that the oscillation of shear stress and heat transport increases as buoyancy force, viscous dissipation and solar radiation increases around each position of heated sphere.